USING EFFECTIVE METHODS TO LEARN GERMAN - Nargiza Siddikova (Journals Park Publishing, 2023)
The article describes the necessity of learning foreign languages, the advantages of learning German, and recommendations for easy and effective learning.
Keywords: language, German, innovation, scientific research, people, country, fashion, discourse.